Implementasi Sikap Multikultural pada Siswa dan Siswi Madrasah Tsanawiyah Nurul Ihsan Kec. Cibinong Kab. Bogor - Edy, Edy (Edusifa: Jurnal Pendidikan Islam, 2022)
This study aims to determine the multicultural attitudes of Madrasah students, to find out whether there is a difference between the multicultural attitudes of students and students in the madrasa, the operational goal is to know what values ​​according to students cannot be implemented properly so that educators are able to provide a stimulus to implementation of these attitudes, functional purpose is for educators to have a reference in the development of multicultural values. The rumors of this research problem are How to Implement Multicultural Attitudes in Madrasah Tsanawiyah students?, Are there differences in multicultural attitudes between students in Madrasahs? The findings of this study are that the average multicultural attitude of madrasah students is very agreeable or very good, this needs to be raised and maintained in the learning process that is related to multicultural values. There is a difference in percentage between male and female students in addressing multicultural attitudes. More in-depth research is needed on the background of why there are differences in multicultural attitudes between men and women Keywords: Education, Multicultural, Madrasa